Pathomechanism of atopic dermatitis in the perspective of T cell subsets and skin barrier functions - "Which comes first, the chicken or the egg?" - Kenji Kabashima (Wolters Kluwer Medknow Publications, 2012)
Atopic dermatitis (AD) is a common skin condition that is characterized by a complex, heterogeneous pathogenesis. The possible candidates for its pathogenesis include skin barrier abnormality and allergy/immunology aspects. It has long been asked, "Which comes first, the barrier dysfunction or the allergy/immunology abnormality?" Recently, direct evidence of a link between the incidence of AD and loss-of-function mutations in the gene encoding Filaggrin has been discovered. This finding suggests that barrier dysfunction is a primary cause of AD. It has also been widely recognized that T cells play an important role in the development of AD in the perspective of the Th1/Th2 paradigm. Recently, however, new T cell subsets, Th17, T22, and regulatory T cells have been identified. In this review, we will update the roles of T cell subsets in AD and ascertain how skin barrier abnormality and allergy/immunology interact in a highly interdisciplinary manner.